The Effect of Work-Life Balance, Work Motivation, and Work Environment on Employee Performance in Medan Petisah - Ini Rahura Harahap; Christi Zepanya Elisabeth Limbong; Friscila Septriyani Hutabarat; Luter Girsang (SEAN Institute, 2026)
Finding out how factors like work-life balance, intrinsic motivation, and the physical workplace affect productivity in Medan Petisah is the primary goal of this research. Research of this kind relies on quantitative methods. Roughly ninety-seven people participated in the study. Multiple linear regression analysis was the technique utilized to analyze the data. According to the t-test results, work-life balance significantly impacts workforce performance (t = 4.959> t table = 1.985, p < 0.05), work motivation significantly impacts workforce performance (t = 5.461> t table = 1.985, p < 0.05), and the work environment significantly impacts workforce performance (t = 6.418> t table = 1.985, p < 0.05). The findings of the F hypothesis test indicate that work motivation, work life balance, and work environment all impact workforce performance. This is supported by a significance value of 0.000<0.05 and a F count value of 61.542> F table 2.703. Coefficient of determination analysis shows that work-life balance, motivation, and work environment all have an impact on workforce performance (with an adjusted R-squared value of 0.654), accounting for 65.4% of the total. Other variables not included in this study accounted for 34.6% of the total influence.